(untitled) (International Educators Conference, 2025)
Effective management of interest rate policy and interest rate risk of banks requires studying its important subjects - loans and deposits, including the central bank and its activities and policies, knowledge of their methods of operation, functions and operations. In order to achieve economic stability, the monetary policy of the Central Bank is of great importance in effectively managing the economy and regulating the money supply in the economy. In the Republic of Uzbekistan, like in many developed countries of the world, there is a two-tier banking system. Its first tier is managed by the Central Bank, which is considered the "bank of banks", which regulates the activities of commercial banks of other forms of ownership and money circulation in the country. The second tier of the banking system is formed by commercial banks of various forms of ownership, which provide credit and settlement services to economic entities, carry out active and passive and intermediary operations. The Central Bank develops the main directions of the monetary policy of the Republic of Uzbekistan, which include analysis and prospective indicators of the economic situation, economically justified limits of the money supply in circulation, and the main directions of interest rate policy.